BRING YOUR OWN DEVICE POLICY AND WI-FI TECHNOLOGY FOR MILITARY EDUCATIONAL ORGANIZATION - Vitalii A. Savchenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
This article explores the concept of combining a Bring Your Own Device (BYOD) policy and Wi-Fi technology with existing information policies and infrastructure for typical Military Educational Organization. In face of financial restrictions many Military Educational Organizations in many countries are expecting a problem of computer renewal. To give employees and students an opportunity to work effectively under impossibility to renovate computer facilities a new BYOD policy has to be applied. This policy is directly connected to development of Wi-Fi infrastructure within organization. Obviously, implementing of BYOD policy in a couple with Wi-Fi technology will allow Military Educational Organizations to include into information process not only existent computer hardware, but a great number of personal devices. Nowadays wireless technologies are forbidden for many military organizations because of information restrictions so all aspects of new approach integrity with Net-Centric strategy, efficiency, reliability, security and cost are considered in the article. This article is based on author’s experience and represents the author’s proposal for the BYOD/Wi-Fi implementation only at the unclassified information environment and the potential financial benefits of this issue.